REVISITING SACRED NARRATIVES: THE PHILOSOPHICAL IMPLICATIONS OF DIGITAL TECHNOLOGY ON THE INTERPRETATION OF ANCIENT DUNHUANG MURALS - Zhang, Yutong (European journal for philosophy of religion, 2024)
The advent of digital technology has revolutionized the way we interact with and interpret cultural heritage. This paper explores the profound philosophical implications of these technological advancements on the reinterpretation of ancient Dunhuang murals, a UNESCO World Heritage site known for its rich Buddhist iconography and historical narratives. By employing digital reconstruction and analysis techniques, scholars and practitioners are able to delve deeper into the textual and visual narratives, revealing previously obscured details and contexts. This study critically examines how digital tools not only enhance visual accessibility but also challenge traditional interpretative paradigms, potentially reshaping our understanding of these murals' religious and philosophical significances. Through a synthesis of empirical research and philosophical inquiry, this paper discusses the transformative potential of digital technology in bridging the past with the present, thereby contributing to a renewed dialogue between ancient wisdom and contemporary philosophical thought.